Prevalence, Activity Limitations and Quality of Life in Patients with Non-Specific Neck Pain in Burundi: A Cross-Sectional Study - Ndacayisaba G; Ndayishima B; Mapinduzi J; Ndayishimiye P; Sinzakaraye A; Van Cant J (Journal of Pain Research)
Gérard Ndacayisaba,1,2 Bénit Ndayishima,3 Jean Mapinduzi,2,4,5 Pierre Ndayishimiye,1,2 Alexis Sinzakaraye,3,6 Joachim Van Cant7 1CNRKR - Centre National de Référence en Kinésithérapie et Réadaptation médicale, Bujumbura, Burundi; 2TechnoRehab Lab2, Filière de Kinésithérapie et Réadaptation, Institut National de Santé Publique, Bujumbura, Burundi; 3Département de Médecine Physique et Réadaptation, Centre Hospitalo-Universitaire de Kamenge, Bujumbura, Burundi; 4CKAO-AMAHORO - Cabinet de Kinésithérapie et d’Appareillage Orthopédique, Bujumbura, Burundi; 5REVAL Rehabilitation Research Center, Faculty of Rehabilitation Sciences, Hasselt University, Diepenbeek, Belgium; 6CAMERHU - Cabinet Médical de Rhumatologie, Bujumbura, Burundi; 7Unité de Recherche en Sciences de la Réadaptation/Rehab Lab, Faculté des Sciences de la Motricité Humaine, Université Libre de Bruxelles, Bruxelles, BelgiqueCorrespondence: Gérard Ndacayisaba, CNRKR - Centre National de Référence en Kinésithérapie et Réadaptation médicale, Bujumbura, Burundi, Tel +257 61 355 482, Email ndacayisaba199065@gmail.comIntroduction: Non-specific neck pain (NSNP) causes a great deal of discomfort, impacting a person’s functionality and quality of life. This study aimed to determine the prevalence, activity limitations, and quality of life in patients with NSNP in Burundi.Patients and Methods: This was a cross-sectional study with descriptive and analytical aims, covering the period from September 2023 to February 2024. It focused on NSNP patients received in three health facilities of Bujumbura. In addition to sociodemographic data, clinical data including pain, disability, psychological status and quality of life were collected.Results: Most of patients (47.1%) were over 40 years old, with an average of 49.30 (13.30) years. The majority was female, married, employed, and had a university education. Most of them (64.70%) described their pain as moderate to severe, with a mean score of 6.20 (1.60) on the numerical scale. A minority had poor health-related quality of life (20.60%). The majority had mild to moderate disability in both the psychological (41.20%) and physical (55.90%) components. Pain location during the current episode had a statistically significant association with social aspects (p=0.049). Individuals with lower levels of education, a more sedentary lifestyle, and greater psychological distress are likely to experience increased activity limitations (p< 0.05).Conclusion: NSNP is a significant public health concern in Burundi, impacting individuals’ socio-professional lives and overall quality of life. Individuals with lower levels of education, a more sedentary lifestyle, and greater psychological distress are likely to experience increased activity limitations. The state of health was perceived as poor by 20.60% of the sample. The physical component of health status was more impaired than the mental component, and the majority of patients presented moderate to severe disabilities, highlighting the need for preventive and management measures to mitigate its impact on individuals and the healthcare system in Burundi.Keywords: non-specific neck pain, prevalence, activity limitations, quality of life, Burundi